PENGARUH KOMBINASI PENGGUNAAN BIOCHAR DAN PUPUK KOTORAN TERHADAP KETERSEDIAAN NUTRISI N, P, K SERTA PERTUMBUHAN JAGUNG (ZEA MAYS L.) PADA TANAH ALUVIAL - Agnes Cyntia Caroline; Rita Hayati; Leony Agustine (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
Alluvial soils are usually dense, so organic matter needs to be added to improve their structure. The purpose of the study was to determine the effect of biochar and manure on the availability of nutrients N, P, K, and corn growth on alluvial soils. The method used in this study is using a complete randomized design with six treatments, namely control (P0), 100% biochar (P1), 100% fertilizer (P2), 75% biochar and 25% fertilizer combination (P3), 50% biochar and 50% fertilizer provision (P4), and 25% biochar and 75% fertilizer (P5) each repeated four times. The results showed that the mixture of biochar from rice husk and chicken manure did not significantly affect soil pH and organic carbon, the mixture had a significant effect on N-total, P-available, K-dd, plant height, and stem diameter of corn plants.